THE EVALUATION OF HIGHER EDUCATION PROBLEMS IN TURKEY - Bertan Akyol; Hasan Arslan (European Scientific Journal, ESJ, 2014)
Higher Education can be defined as all of the educations in the national education system, after secondary education, at least the last four semesters. It can be considered as a symbol of national prestige and each country wishes to ensure that higher education functions effectively and efficiently to avoid losing prestige. In Turkey, universities’ efficient and effective functioning seems to be not achieved according to the many authors. So, a deeper examination of the Turkish education system and its stakeholders’ interests on higher education through a systematic approach has been aimed in this study. The problems of higher education in Turkey has been analyzed from three main perspectives; purpose, process and structure. In purpose dimension, it has been found out that the purposes of higher education in Turkey are in contradiction. For the, process dimension, it has been seen that higher education institutions face to autonomy problems. Lastly for the structure dimension, the problem that university lecturers and students experience and the issues as the output of higher education system has been analyzed. According to the literature, studied and reports on the problems of Turkish higher education system, it has been found out that the higher education system in Turkey is facing many problems which need to be minimized for the system to be effective.